Perancangan Sistem Informasi Pendataan Penduduk Nonpermanen Berbasis Website Pada Kecamatan Prambon Kabupaten Sidoarjo - Erfina, Idha Maharani; Findawati, Yulian; Dijaya, Rohman (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The Prambon Subdistrict Office is a Regional Government Organization in the Sidoarjo Regency area that has the authority to conduct a census of nonpermanent residents in its jurisdiction. The office has never conducted a census of nonpermanent residents before and is facing challenges in initiating the process. However, the data on the number of nonpermanent residents is crucial for their operations. To address this issue, the author is interested in developing an Information System for Nonpermanent Resident Census. The development of this information system will follow the waterfall methodology, which involves a sequential and linear approach to software development, ensuring comprehensive results. The system will be designed as a website, utilizing the CodeIgniter framework and the PHP programming language. The database used for this system will be MySQL. To ensure the system's functionality and accuracy, it will be tested using black-box testing, a method where the internal structure of the system is not known to the tester. The resulting Information System for Nonpermanent Resident Census will serve as a solution for the Prambon Subdistrict Office in conducting a census of nonpermanent residents within its jurisdiction. It will also provide valid population reports, specifically for nonpermanent residents.